KEMAMPUAN KOMUNIKASI MATEMATIS DITINJAU DARI MOTIVASI BELAJAR PADA MATERI HIMPUNAN DI SMPN 14 PONTIANAK - Verawati, Verawati; Jamiah, Yulis; T, Ahmad Yani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis study aims to find out how studentsâ€™ mathematical communication skills in solving questions on set material that have high, medium and low learning motivation in SMP Negeri 14 Pontianak. The mmethod in this research is descriptive qualitative descriptive research form. Data collection techniques used are measurement techniques and direct communication. Data collection tools used in this study were questionnaires, written tests and interviews. Obtained that student with high learning motivation are able to ekspress and understand mathematical ideas, and can use mathematical notation and draw venn diagrams. Students with learning motivation are able to ekspress mathematical ideas in the form of writing set notations, but they are not quite right in describing venn diagrams, while students are less able to ekspress and understand mathematical ideas so that they cannot draw venn diagrams. Students with low learning motivation find ini difficult to understand the commands of the questions and are less able to solve the given problems. Â Keywords : Learning Motivation, Mathematical Communication SkillsÂ